Predicting intention to visit kopitiams as halal food outlet: An extension of the theory of planned behavior - Ishak, Mohd Sobhi; Ahmad, Muhammad; Abdul Rahman, Mohd Nizho; Rofie, Mohamad Khadafi (2013)
Eating and hangout at modern Kopitiams has become a life culture especially among younger generation.This study extended Theory of Planned Behavior (TPB) model to explain the formation of young Muslims’ intentions to visit Kopitiams outlet as Halal food outlet.Perceived Kopitiams as a Halal outlet and awareness of Halal food was tested as a mediating factor to the relationship between attitude, subjective norm, and perceived behavioral control with the intentions.A total of 118 university students participated and answered questionnaires in a cross-sectional study. Data was analyzed using partial least squares.Results showed that attitude and subjective norm but not perceived behavioral control was found to have a significant direct effect to the prediction of intention.Further, multiple mediator bootstrap analysis indicated that perceived Halal outlet significantly mediate the subjective norm and perceived behavioral control on intention to visit Kopitiams.The results of this study could provide useful insights to the food outlets provider and religious authorities.